The Increase of Brain-Derived Neurotrophic Factor Expression after Moderate-Intensity Aerobic Exercise in Obese Women - Gumelar, Rixco Gesang; Sugiharto, Sugiharto; Merawati, Desiana; Nowak, Agnieszka Magdalena; Pranoto, Adi (Faculty of Sport and Health Sciences, 2024)
Obesity is closely related to a decrease in brain-derived neurotrophic factor (BDNF) expression, which will pose a risk for metabolic disorders. Therefore, this study aims to prove the effect of moderate-intensity aerobic exercise on increasing BDNF expression in obese women. A total of sixteen obese women were selected based on predetermined criteria and were divided into 2 groups, namely the aerobic exercise group (AE) and the control group (CN). Aerobic exercise was carried out by running on a treadmill at moderate intensity (60-70 HRmax) for 40 minutes/session with a frequency of 5x/week for 2 weeks. Blood samples were taken twice before and after exercise intervention to see BDNF expression using the Enzyme-Linked Immunosorbent Assay (ELISA-kit) method. The results of the analysis showed differences in increase between the control group (1816.66 ± 689.48 vs. 1822.86 ± 467.87 pg/mL; p = 0.974) and the intervention group (2173.81 ± 705.89 vs. 3635.01 ± 699.71 pg/mL; p = 0.013). This shows that moderate-intensity aerobic exercise carried out for 2 weeks has proven effective in increasing BDNF expression in obese women.